Correction: Surgical Site Infection after Craniotomy in Neuro-Oncology (SINO): A protocol for an international prospective multicentre service evaluation across the United Kingdom and Ireland. - Keng Siang Lee; Balint Borbas; Daoud Chaudhry; Ashvin Kuri; Lawrence Best; Conor S Gillespie; Hakim-Moulay Dehbi; Kristian Aquilina; Paul Brennan; Puneet Plaha; Keyoumars Ashkan; Michael D Jenkinson; et al. (PLoS ONE)
[This corrects the article DOI: 10.1371/journal.pone.0316237.].